Badiou and Plato : an education by truths - Bartlett, A. J. (Adam John), 1967- (Edinburgh University Press, 2011)
An interrogation of Plato's entire work using the concepts and categories of Alain Badiou. This is the first book to critically address and draw consequences from Badiou's claim that his work is a 'Platonism of the multiple' and that philosophy today requires a 'platonic gesture'. Examining the relationship between Badiou and Plato, Bartlett radically transforms our perception of Plato's philosophy and rethinks the central philosophical question: 'what is education?' Key Features. Corrects many errors in the existing commentary on Badiou's work Extracts a key Platonic theme crucial at every level of culture today: education